SIZING PROCESS FOR 2D REINFORCED CONCRETE STRUCTURES BASED ON THE DIRECT EVALUATIONOF STRESS TENSORS - Souza, Marcus V. S.; Araújo, Francisco C. de (Revista Interdisciplinar de Pesquisa em Engenharia, 2018)
In this paper, a general strategy for sizing plane surface reinforced concrete structures is proposed, which takes into account the direct evaluation of stress tensors in a number of points of the framework structure. Thus, it has the advantage of being applicable also to size structural elements whose responses are not given in terms of stress resultants as e.g in 2D reinforced concrete walls or 3D solid elements. Particularly in this paper, we apply the technique proposed to size the shear reinforcement in 2D framework elements, while the bending reinforcement is calculated by the classical process for line concrete elements. Additionally, we present a computer-aided design platform that integrates the structural analysis and the sizing process. The code offers options of modeling 2D frames with complex cross-section geometries and varying rigidities along the axis of the elements.